ETOS DAGANG DALAM PERSPEKTIF PEMIKIRAN ORANG ISLAM JAWA (Studi terhadap Serat Darmalaksita Karya Mangkunegara IV) - Daryono Daryono (JURNAL ILMIAH EDUNOMIKA, 2023)
This article is based on the results of library research (library research) which aims to understand the trade ethos from the perspective of Javanese Muslim thought as stated in Serat Darmalaksita, one of Mangkunegara IV's works. The method of analysis through socio-historical and normative, normative ethics as well as meta-ethics can understand the theoretical construction of the Javanese Muslim trade ethos as a system of Islamic objectification through three ways of being kind: being respectful and caring for everything, being respectful and harmonious and caring for anyone and according to the culture or religious experience of Javanese Muslims in that condition. These three ways of being kind were practiced during Mangkunegara IV. On the one hand, the practice of his trading ethic is proven, even though it is different from the morals of capitalism. However, on the other hand, it was able to achieve humane progress in various fields of life so that the Mangkunegaran kingdom was known as Kala Sumbaga (prosperous era). Therefore this theoretical construction might be an alternative thought as an ethical vision in the field of trade at the regional or national level. Keywords :Ethos, Trade, Darmalaksita Fiber, Islam, Java